TAX LEARNING IN THE DIGITAL ERA: EFFECTIVENESS AND CHALLENGES AT MERCU BUANA UNIVERSITY - Anisa Millenia Dewi; Febrian Kwarto (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
Fast digitalized learning has resulted in greater embrace of online learning in higher education systems, even on complex topics like taxation. This change implies the need for the assessment of the impact and hurdles facing internet based tax education. This study aims to evaluate the effectiveness of online tax learning in the context of higher education. The research method used is quasi-qualitative, involving participants enrolled in an online tax course. The analysis technique employed is Creswell's spiral analysis. The findings indicate that online tax learning offers students flexibility in access and scheduling, enhances engagement, and provides advantages in the application of technology. However, challenges such as difficulties in accessing technology and a lack of direct interaction may impact the effectiveness of learning. The implications of this study provide insights for the development of further learning strategies and curriculum updates that support the effectiveness of online tax education in higher education institutions.